KAJIAN KERAGAMAN GENETIK GEN PENYANDI NADH Dehydrogenase Sub-unit 6 (ND6) PADA Tarsius spectrum DAN Tarsius dianae - , ANTONOV AFIKANA, DR. drh. Rini Widayanti, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tarsius is one of Indonesiaâs primate species which are threatened to extinction. Morphological and anatomical homology among the species complicate the identification, classification and conservation. These objectives, it required a relatively accurate technique to distinguish those species up to molecular genetics level. The main objective of this research is to analyze the genetic diversity in Tarsius sp. based on sequences of NADH dehydrogenase subunit 6 (ND6) encoding gene. DNA samples are isolated from bicep femoris muscle of three Tarsius spectrum from Airmadidi, Nort of Celebes and a Tarsiusdianae from Center of Celebes. DNA Samples than amplificated with Polymerase Chain Reaction (PCR) technique used ND6F lama and ND6R. Amplification process produces PCR 621 bp which than sequenced. Sequencing result then analyzed using MEGA 5.05 version program and compared with some other Tarsius sp. species obtained from Genbank. Analysis result showed that the genetics distance between Tarsius spectrum and Tarsius dianae is 4.7% and based on the amino acid sequence is 1.8%. The phylogram which is using neighbor joining method based on nucleotide sequences and amino acid sequences of ND6 can be used to differentiate of Tarsius spectrum and Tarsius dianae, it is support by 100% bootstraps value. Sequence on ND6 region could be used to differentiate Tarsius dianae and Tarsius spectrum.